Pengaruh Variasi Kuat Arus Listrik Terhadap Kekuatan Tarik Hasil Pengelasan Tungsten Inert Gas (TIG) Pada Material Aluminium 5052: 1. PENDAHULUAN, 2. METODE, 3. HASIL DAN PEMBAHASAN, 4. KESIMPULAN DAN SARAN, UCAPAN TERIMAKASIH, DAFTAR RUJUKAN - Abdi Ciputra; Ni Made Novia Kusumayani; Edi Elisa (Jurnal Pendidikan Teknik Mesin Undiksha, 2026)
Technological advances in the field of welding continue to develop, especially in the Tungsten Inert Gas (TIG) method which is widely used to join metals such as Aluminum 5052. This study was conducted to examine the effect of differences in electric current on the mechanical properties of welding results, including tensile strength, strain, and modulus of elasticity, using ER4043 electrodes and CO₂ shielding gas and ASTM E8 standard specimens. The approach used was a quantitative experiment with variations in current of 90A, 100A, 110A, and 120A, then tested using a tensile testing machine and analyzed through data presentation in the form of tables and graphs. The test results showed that a current of 100A provided the highest tensile strength value of 79.242 MPa, while a current of 120A produced the largest strain of 0,0174 which indicates a more ductile material. Meanwhile, the highest modulus of elasticity value was obtained at a current of 100A of 20,614 GPa which indicates the best level of material stiffness. In general, current variations significantly affect the mechanical characteristics of the weld, with currents that are too low resulting in less than optimal penetration, while currents that are too high can potentially cause overheating and weld defects. Therefore, determining the appropriate current is a crucial factor in achieving optimal weld joint quality.